Computational Fluid Dynamics for CO2 Utilisation to Valuable Products in Flow Reactors - Harkou, Eleana (My University, 2025)
The objective of the present work is to study theoretically the CO2 hydrogenation in several continuous flow reactor designs and materials as the worldwide high demand of energy is contributing to the reinforcement of global warming in the environment. CO2 present in gas emissions from various technologies and applications should be separated and further stored or utilised. The recent years, with great effort, the scientific community endeavours to give a solution to all the limiting factors that are associated with the CO2 hydrogenation. Considering the above, the main aim of this work is to evaluate, understand and optimise, using computational fluid dynamics (CFD) simulations, the performance of the hydrogenation processes.
Keywords: CFD modelling; CO2 hydrogenation; CO2 methanation; reactor design